Influence of an Earth Dam Cut-Off Plastic Concrete Component on Its Physical Properties - Kazemian, Sina; Ghareh, S. (AMER SOC CIVIL ENGINEERS, 2016)
Plastic concrete is a suitable material for building earth dam cut off due to low permeability, high deformability and enough strength to withstand applied stresses. Due to the lack of a specified standard for plastic concrete materials, evaluation of the effect of the amount and quality of materials such as concrete aggregates (fine and coarse gravel and sand), cement, water and bentonite on the mechanical properties of plastic concrete is considered to be a serious need. In this study, we have investigated the effect of the ratio of mixing materials (mixture proportions) and cement as well as the materials' quality such as the type of bentonite on compressive strength and modulus of plastic concrete elasticity. The results of this study showed that by decreasing the ratio of term activity, compressive strength will be reduced due to increasing free water in case of the stability of other parameters. However, the effect of aggregates unlike cement has no direct effect on mechanical properties of plastic concrete.